Ana Mendieta : Earth Body : sculpture and performance 1972-1985 - Whitney Museum of American Art, New York New York; Miami Art Museum Miami; Hirshhorn Museum and Sculpture Garden Washington; Des Moines Art Center Des Moines; Brett, Guy; Herzberg, Julia P.; Iles, Chrissie; Rifkin, Ned; Roulet, Laura; Viso, Olga M. (Ostfildern-Ruit Washington : Hatje Cantz Verlag Ostfildern-Ruit Hirshhorn Museum and Sculpture Garden Washington, 2004)
This lavishly illustrated volume tracing the brief yet prolific career of Ana Mendieta examines her production within the social and artistic fabric of the 1970s and 1980s and reveals her lasting legacy. Heretofore unpublished research gained from exhaustive study of previously unavailable archives, site visits, and extensive interviews allows for the first truly comprehensive biography of the artist. The development of Mendieta's art from early performances and actions to later sculptures and objects, all rooted in nature and the body is traced through texts and images that reveal her complex relationship to Mexico, her native Cuba, contemporary Latin American art, and the international art world. Distinguished by the singular hybrid art form she created - earth-body work - her films, photographs, and actions feature the artist's body work, or its haunting silhouette, in the studio, merged with the landscape, etched on a leaf or burned into soil or a tree trunk. Born in Havana, Mendieta came to the United States without her parents at twelve years of age. Following this painful experience of exile, she quickly absorbed aspects of North American culture while vehemently asserting her identity. She incorporated symbols appropriated from ancient and indigenous cultures of Africa, Europe, and the Americas into a contemporary practice informed by conceptual and process-oriented art and the women's art movement. Though deeply rooted in her own life experience, Mendieta's art reveals her passionate desire to address concerns that affect our society as it struggles with correspondences and differences between individuals, nations, and cultures.
Checklist of the exhibition p. 272-279
Notes p. 240-259
bibliog. p. 266-271
biog. p. 224-239
ind. tent., gr. tent. p. 260-265
Engels
Keywords: Mendieta, Ana